The Effect of Information and Communication Technologies on Urban Structure. - Ioannides, Yannis Menelaos.; Overman, Henry G.; Rossi-Hansberg, Esteban.; Schmidheiny, Kurt. (Tufts University. Tisch Library., 2016)
This paper examines the effects of information and communication technologies (ICT) on urban structure. Improvements in ICT may lead to changes in urban structure, for example, because they reduce the costs of communicating ideas from a distance. Hence, they may weaken local agglomeration forces and thus provide incentives for economic activity to relocate to smaller urban centres. We use international data on city size distributions in different countries and on country-level characteristics to test the effect of ICT. We find robust evidence that increases in the number of telephone lines per capita encourage the spatial dispersion of population in that they lead to a more concentrated distribution of city sizes. So far the evidence on internet usage is more speculative, although it goes in the same direction. We argue that the internet is likely to have similar, or even larger, effects on urban structures once its use has spread more thoroughly through different economies.